2006
DOI: 10.1007/s10856-006-0185-8
|View full text |Cite
|
Sign up to set email alerts
|

Tissue reaction and surface morphology of absorbable sutures after in vivo exposure

Abstract: Tissue reaction to suture materials depends mainly on how the polymer they are composed of interacts with the tissues. There are few in vivo studies evaluating the suture material modifications resulting from its interaction with tissues. This paper aimed to study rat subcutaneous tissue reaction to irradiated polyglactin 910, polydioxanone, poliglecaprone 25 and chromic gut and its correlation with the ultra-structural alterations the materials undergo. The histological alterations were studied on the 1st, 2n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 27 publications
4
36
0
1
Order By: Relevance
“…When the values of the suture materials on days 2, 4 and 8 were compared for both Z1 and Z2, the only significant difference was found on day 8 for both zones (Tables 2 and 3 3,28,29 Even though no significant differences were found between the Z1 and Z2 values of catgut between the days 2, 4 and 8, catgut ranks the second among other suture materials with its mean diameter values. Dacron suture presented the highest diameter scores for both Z1 and Z2 and is followed by silk.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…When the values of the suture materials on days 2, 4 and 8 were compared for both Z1 and Z2, the only significant difference was found on day 8 for both zones (Tables 2 and 3 3,28,29 Even though no significant differences were found between the Z1 and Z2 values of catgut between the days 2, 4 and 8, catgut ranks the second among other suture materials with its mean diameter values. Dacron suture presented the highest diameter scores for both Z1 and Z2 and is followed by silk.…”
Section: Discussionmentioning
confidence: 93%
“…Polyglactin 910 also enabled the organization of fibrous connective tissue around itself at late phases, showing a similar behavior as reported by Nary Filho et al 28 With regard to polyglactin 910, Andrade et al observed that chromic gut had induced tissue necrosis and more granulation tissue formation. 3 According to Racey et al, catgut sutures started to disappear by the fifth day and were totally absorbed after 7 days, but the inflammation reaction did not completely vanish. 25 Yaltirik et al, 29 compared the tissue reaction effects of different suture materials in the soft tissues of rats and stated that polyglactin 910 had produced the mildest tissue reaction among the test materials.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing use of PDO nano-fibers for cosmetic and other purposes [4][5][6][7][8][9][10] makes it imperative to understand its effect on the immune system. Our data suggests that PDO has no adverse effect on the functions of PMNs, monocytes and NK cells in humans ( Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…In alternative medicine, PDO nano-fibers are currently being used for the treatment of chronic inflammatory diseases [4,5,9,10]. According to Park [11], acupuncture with PDO needles resulted in improvements in pain and swelling in patients suffering from knee joint pain with edematous knee and other joints.…”
Section: Introductionmentioning
confidence: 99%
“…There are few in vivo studies evaluating the tissue reaction to suture materials that mainly depend on how the suture polymer interacts with the tissues. 11 Non-absorbable sutures include silk (now infrequently used) and several synthetic materials designed for elasticity, easy handling, good knot security and minimal tissue irritation.…”
Section: Discussionmentioning
confidence: 99%